2015
DOI: 10.1159/000377677
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Ecology of Propithecus verreauxi in Kirindy Mitea National Park

Abstract: The locomotor behaviour of 2 groups of Propithecus verreauxi (Verreaux's sifaka) was studied over an 8-month period in Kirindy Mitea National Park (KMNP), Madagascar. This paper assesses the major characteristics of their locomotion, focusing on the extent that seasonal variation in climate and habitat, and local variation in habitat, is reflected in changes in locomotor behaviour. P. verreauxi is a committed leaper with a strong preference for vertical and angled supports. We found clear between-group differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, we note that locomotor differences potentially affected travel and rest data. As a vertical clinger and leaper, Propithecus moves with shorter, high‐velocity leaps interspersed with rest (Furnell et al, 2015); the quadrupedal Eulemur is more continuously “on the move” when traveling. Instantaneous sampling may therefore provide a misleading comparison.…”
Section: Discussionmentioning
confidence: 99%
“…However, we note that locomotor differences potentially affected travel and rest data. As a vertical clinger and leaper, Propithecus moves with shorter, high‐velocity leaps interspersed with rest (Furnell et al, 2015); the quadrupedal Eulemur is more continuously “on the move” when traveling. Instantaneous sampling may therefore provide a misleading comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence for this explanation comes from VCL lemurs. Although indriids (especially Propithecus ) are vertical clingers and leapers, larger‐bodied species like Indri indri are also skilled hangers, engaging in bimanual and especially bipedal suspension, using highly abducted hip postures in a variety of activities (Furnell, ). Indeed, if we separate Indri indri from the other VCLs of this study (results not shown here) we observe that their femoral head diameters are higher than the other VCL lemurs and close to Varecia .…”
Section: Discussionmentioning
confidence: 99%
“…Verreaux's sifaka have adapted to periods of seasonal resource depression (Norscia et al, 2006), as well as occasional supra‐annual depression events (cyclones: Lewis & Bannar‐Martin, 2012, droughts: Lawler et al, 2009; Veilleux & Lewis, unpublished data, fires: Axel, 2018) by decreasing active period, activity level, and daily path length during the dry season (Erkert & Kappeler, 2004; Furnell et al, 2015; Norscia et al, 2006; Rudolph et al, 2019). Accounts of ranging patterns at the home range scale are not as consistent, however, even in the same population.…”
Section: Introductionmentioning
confidence: 99%